Impact of measurement uncertainties on determination of chlorophyll‐specific absorption coefficient for marine phytoplankton1. Issue 12 (30th December 2014) - McKee, David; Röttgers, Rüdiger; Neukermans, Griet; Calzado, Violeta Sanjuan; Trees, Charles; Ampolo‐Rella, Marina; Neil, Claire; Cunningham, Alex
Abstract Understanding variability in the chlorophyll‐specific absorption of marine phytoplankton, aph*Chl (λ), is essential for primary production modelling, calculation of underwater light field characteristics, and development of algorithms for remote sensing of chlorophyll concentrations. Previous field and laboratory studies have demonstrated significant apparent variability in aph*Chl (λ) for natural samples and algal cultures. However, the potential impact of measurement uncertainties on derived values of aph*Chl (λ) has received insufficient study. This study presents an analysis of measurement uncertainties for a data set collected in the Ligurian Sea in Spring and assesses the impact on estimates of aph*Chl (λ). It is found that a large proportion of apparent variability in this set of aph*Chl (λ) can be attributed to measurement errors. Application of the same analysis to the global NOMAD data set suggests that a significant fraction of variability in aph*Chl (λ) may also be due to measurement errors.